Preparation of hollow TiO(2) nanoparticles through TiO(2) deposition on polystyrene latex particles and characterizations of their structure and photocatalytic activity - Wang, Jingang (Springer, 2012)
In a mixed solvent of water and ethanol, polystyrene/titanium dioxide (PSt/TiO(2)) composite particles of core-shell structure were prepared by hydrolysis of tetrabutyl titanate in the presence of cationic PSt particles or anionic PSt particles surface-treated using γ-aminopropyl triethoxysilane. Hollow TiO(2) particles were obtained through calcination of the PSt/TiO(2) core-shell particles to burn off the PSt core or through dissolution of the core by tetrahydrofuran (THF). An alternative process constituted of preheating the PSt/TiO(2) particles at 200°C to allow partial crystallization followed by calcination or PSt dissolution by THF. The outcome TiO(2) particles thus prepared were examined by TEM, and hollow TiO(2) particles were observed. The crystalline phase structure and phase transformation were characterized, which revealed that preheating before the removal of the PSt core was useful to achieve the desired hollow TiO(2) particles, and the calcination process was beneficial to the formation of anatase and rutile structures. The tests of TiO(2) particles as catalyst in the photodegradation of Rhodamine B demonstrated that a much higher catalytic activity was observed with the TiO(2) hollow particles prepared through calcination combined with preheating.